Analisis kontrastif struktur asas ayat bahasa Arab dan Melayu / Baharuddin Shahman - Baharuddin, Shahman (2012)
The topic studied is about “ BASIC STRUCTURAL CONTRASTIVE ANALYSIS OF ARABIC AND MALAY SENTENCES ” , is subject that important to find any similarities and differences between both of those languages. This results of this servay could add more understanding and mastery of Arabic as second language beside their mother tongue. This study aimed to proffer clearer exposure and deep understanding to students and teachers of basic structure between Arabic and Malay language. However, the study is especially to explan the basic Arabic sentences, and explaining the basic forms of the Malay language, identify similarity and the differences between Arabic and Malay language and give further exposure and understanding that easier way to understand and mastery of Arabic. This study also divided into seven chapters. Chapter one is the introduction on study that will be implemented, which related to research background, study problems, study scope, objectives, study survey which related to the method and pedagogy also the framework that arranged. Author will elaborate in chapter two matters related to contrastive analysis's introduction and a few of linguistic member's opinion on definition, history and theories which related. While in the chapter three, will explain on subject introduction and predicate in Arabic and Malay language and the association between languages. In chapter four, author would be administering introduction on construction basic of Arabic sentences by giving related examples. While in chapter five on the other hand, expose on construction of basic introduction of the Malay language sentences and giving related examples. In chapter six is emphasis on study contrastive that operating from the similar aspect between Arabic and Malay language and describe the differences which occurred between both languages. This chapter is very important to be observed. In chapter seven, author will make a conclusion and several proposals that could be apply and executed by certain parties to realise aim of this study to give understanding and mastery of Arabic among teachers and students.